HUBUNGAN ANTARA PENERANGAN DI TEMPAT KERJA DAN KARAKTERISTIK PEKERJA DENGAN KELUHAN KELELAHAN MATA PADA PENJAHIT BORDIR DI CV.X BANGIL-PASURUAN - Dhita Makhsunah Purwaningtyas (UNUSA Press, 2021)
Improper lighting that is not according the standards may result in health problems, one of which is eyestrain, a visual disturbance. Eyestrain is one result of improper lighting that is not according to standards. In addition, the characteristics of workers also play a role in the occurrence of eyestrain. The purpose of this study is to determine the relationship between the lighting in a workplace and the characteristics of workers with complaints of eyestrain in embroidery tailors at CV